Academic Audit-A Tool for Enhancing Teaching-Learning Effectiveness - Telsang, Martand T.; Kulkarni, Sushma S. (Journal of Engineering Education Transformations, 2011)
The institutions for their survival and growth have to impart education that will meet the ever increasing demand of employers, coupled with the attitude of lifelong learning in students. This paper aims to discuss the case study of an engineering college situated in rural Maharashtra, which has made a mark at the National Level through the implementation of innovative and best practices like Academic Audit and Faculty Competency Mapping. The process of Academic Audit captures the classroom dynamics in an environment of ease and comfort. Class room dynamics here refers to delivery effectiveness, learning experience of students with different learning preferences and styles, factors that hinder the effectiveness of both teaching and learning. A detailed audit process is laid down including the guidelines to auditors and post audit counseling to faculty. The audit is designed to capture the five important dimensions of a teacher, namely-subject knowledge, preparation, communication, class control and concern for students and opportunity to interact. The audit process is going to map the individual teacher and the course on a 10 point scale with appropriate weights for the five dimensions. Weightages for dimensions are decided based on the opinions of the senior faculty and academicians Based on the scores, the faculty competency enhancement is planned and appropriate actions are initiated to train the faculty in the specified dimensions. The outcome of the audit is evident in terms of improved learning outcomes, enhancement of teaching deliveries and competency, collaborative learning, good academic environment. This process is a pre step in consolidating teaching learning process resulting in better quality.